THE INFLUENCE OF HOLISTIC FEED ON PERFORMANCE OF SUPER NATIVE CHICK - Supriyanto Supriyanto; Budi Purwo Widiarso; Sucipto Sucipto; Fabiana Mentari (Jurnal Kedokteran Hewan, 2021)
This study determines effects of raw material feed (derived from corn, bran, soybean pods, concentrates and Indigofera zollingeriana local to Magelang) on the performance of native chicks. Performance was measured by feed consumption, body weight gain, Feed Conversion Ratio (FCR), mortality, and morbidity. This experiment used Completely Randomized Design (CRD) with three different feed treatments, and each treatment consisted of 30 free-range female chicks as replicants, from 0-4 weeks old. Super native chick feed was formulated by trial and error by mixing all ingredients: corn, bran, soybean pods, Indigofera zollingeriana, and premix. After mixing, a proximate test determined the nutritional content of the feed. Feed was then administered to chicks. Quantity of feed was administered according to age. The results obtained in the study were analyzed descriptively and statistically using the Variance Test (ANOVA) for the variables of body weight gain, feed consumption, and FCR. The Kruskal Wallis test was used via SPSS 26 program for mortality and morbidity variables with three treatments (T1, T2, and T3) and three replications. Each treatment consisted of 30 research individuals. Results showed that the super native chicks on varied protein diets had a significant difference in performance (P0.05), with feed 3 performing the best feed 3 produced a feed consumption of 430.20 g/chick and body weight gain of 174.67 g/chick, along with 2.46 FCR, 0% mortality, and 3.33% morbidity. The conclusion this study is holistic feed made from local ingredients with the addition of Indigofera zolliengeriana had a significant effect on increasing average daily gain, increasing feed consumption, and reducing feed conversion ratio (FCR)  in native super chick.